Inovasi Hijau: Sinergi Budidaya Maggot untuk Kemandirian Masyarakat - Fadli, Hanif; Fauziah, Rizka; Larasati, Aulia Nadhila; Pratama, Naufal Aldian; Fahrudin, Rafif Eka; Romadhoni, Muhammad Ilham; Jauharah, Tiffany; Lestari, Febri; Naufal, Muhammad Rikza; Niandy, Zakariya Ahmad; Kesetyaningsih, Tri Wulandari (Universitas Muhammadiyah Yogyakarta, 2025)
The Special Region of Yogyakarta faces serious challenges in organic waste management. This waste originates from households, markets, and food MSMEs, which are often poorly managed, leading to environmental and health problems. This community service program aims to increasing knowledge, awareness, and skill regarding to waste management through the application of green innovation. The main focus of the program is the cultivation of Black Soldier Fly (BSF) maggots as an efficient and sustainable organic waste management solution, as well as the utilization of Indonesian spices to improve the community's economy. The community is actively involved in every stage of the program, from problem identification to implementation. The method used in this program was education on household organic waste management, training in maggot cultivation, and processing spices into value-added products. The program's success is measured by several indicators, including the increased number of participants actively engaged in maggot cultivation and spice processing, as well as the improvement of community awareness and skills in maggot farming and the utilization of Indonesian spices. The results showed that this program increasing the community’s knowledge and awareness regarding the importance of waste management and the economic potential of spices. The community has also acquired new skills in maggot cultivation and spice processing, resulting in innovative products such as organic fertilizer, animal feed, herbal drinks, and cooking spices. Additionally, joint business groups have been formed, strengthening the community's economy and expanding market access. This program demonstrates the effectiveness of the synergy between maggot cultivation and spice utilization in achieving community self-sufficiency and environmental conservation